Is Hypertrophic or Keloid Wound Scar a Risk Factor for Stricture at Esophagogastric Anastomosis Site after Esophageal Cancer Operation? - Yong Won Seong; Jee Hyun Kim; You Jung Ok; Se Jin Oh; Jae-Sung Choi; Jeong Sang Lee; Hyeon Jong Moon (The Korean Journal of Gastroenterology, 2022)
Background/Aims: Anastomotic stricture at the esophagus and the conduit anastomosis site after the surgical resection of esophageal cancer is relatively common. This study examined whether a hypertrophic scar or keloid formation at a surgical wound is related to an anastomotic stricture. Methods: From March 2007 to July 2017, 59 patients underwent curative surgery for esophageal cancer. In 38 patients, end-to-end anastomosis (EEA) of the esophagus and the conduit was performed using EEA 25 mm. A hypertrophic wound scar was defined when the width of the midline laparotomy wound scar exceeded 2 mm. The relationship between the hypertrophic scar and stricture and the other risk factors for anastomotic stricture in these 38 patients was analyzed. Results: Of the 38 patients, eight patients (21.1%) had an anastomotic stricture, and a hypertrophic skin scar was observed in 14 patients (36.8%). Univariate analysis revealed lower BMI and hypertrophic scars as risk factors (p=0.032, p=0.001 respectively). Multivariate analysis revealed a hypertrophic scar as an independent risk factor for an anastomotic stricture (p=0.010, OR=27.06, 95% CI 2.19-334.40). Conclusions: Hypertrophic wound scars can be a risk factor for anastomotic stricture after surgery for esophageal cancer. An earlier prediction of anastomotic stricture by detecting hypertrophic wound healing in patients undergoing esophagectomy may improve the patients’ quality of life and surgical outcomes by earlier treatments.